"'Are you blind, Lord Thomas, or can't you very well see?': An Interpretation of Death in the Newfoundland Classical Ballads" - Peere, Isabelle (CELAT, Université Laval, 1989)
peer reviewed A talerole analysis of the Newfoundland Child ballad corpus dealing with death, suggesting how death can be avoided and overcome, or these songs' concern with life as 'strategies for survival'.